A Hyperthermophilic Argonaute From Ferroglobus placidus With Specificity on Guide Binding Pattern - Guo, Xiang; Sun, Yingying; Chen, Liuqing; Huang, Fei; Liu, Qian; Feng, Yan (Frontiers in Microbiology, 2021)
Argonaute proteins (Agos) from thermophilic archaea are involved in several important processes, such as host defense and DNA replication. The catalytic mechanism of Ago from different microbes with great diversity and genome editing potential is attracting increasing attention. Here, we describe an Argonaute from hyperthermophilic Ferroglobus placidus (FpAgo), with a typical DNA-guided DNA endonuclease activity but adopted with only a short guide 15–20 nt length rather than a broad guide selectivity for reported Agos. FpAgo performed the precise cleavage of phosphodiester bonds between 10 and 11 nt on the target strand (counting from the guide strand) guided strictly by 5′-phosphorylated DNA at temperatures ranging from 75 to 99 °C. The cleavage activity was regulated by the divalent cations Mn2+, Mg2+, Co2+, and Ni2+. In addition, FpAgo possesses guide/target mismatch tolerance in the seed region but is sensitive to mismatches in the 3′-guide region. Notably, the EMSA assay revealed that the FpAgo-guide-target ternary complex exhibited a stronger binding affinity for short 15 nt and 16 nt guide DNAs than longer guides. Moreover, we performed structural modeling analyses that implied the unique PAZ domain of FpAgo for 3′-guide recognition and binding to affect guide length specificity. This study broadens our understanding of thermophilic Agos and paves the way for their use in DNA manipulation.